UPAYA PENINGKATAN PEMEREKAN ORGANISASI BERBASIS DARING MELALUI PELATIHAN MENGEMBANGKAN MEDIA SOSIAL RPTRA DHARMA SUCI - Michael Christian (Universitas Bunda Mulia, 2017)
The regulation of the Governor of DKI Jakarta Number 196 (2015) on Child Friendly Integrated Public Space (RPTRA) explains the open areas for children that can be a positive medium for interaction and play. The development of RPTRA in DKI Jakarta is not fully funded by the DKI Jakarta government through the Regional Government Expenditure Budget (APBD), but the program also involves companies in the form of Corporate Social Responsibility (CSR). In terms of marketing, this synergy program can not only strengthen the organizations/companies involved in the CSR program but indirectly can help the existing RPTRA to more easily introduce the implementation of its activities through branding. The concept of branding for the organization is not an easy thing not only for the surrounding community as RPTRA's board but also for marketers. Social networking sites can be a powerful medium in developing RPTRA as an organizational brand that makes marketing communications have a significant influence on how organizations communicate to their customers. This study aims to measure the effectiveness of training on the role of social media to improve online organization. The method used by observation measurement at two periods (before and after training) and the effectiveness of training provided (using SPSS 22.0). The result of this training is able to explain the increasing effectiveness of the use of social media RPTRA Dharma Suci and utilization of supporting media elements in it such as photos, videos and so on. Suggestions for further research may consider the use of other social medias and observations over a longer time span.Keywords: RPTRA, branding, organization, social media